105 The Effect of Socioeconomic Status on Gross Total Resection, Radiation Therapy, and Overall Survival in Patients With Gliomas. (1st August 2016) - Deb, Sayantan; Pendharkar, Arjun Vivek; Altekruse, Sean; Ratliff, John K.; Desai, Atman
Abstract: INTRODUCTION: Socioeconomic status (SES) is associated with survival in many cancers but the effect of SES on survival and access to care for patients with gliomas has not been studied. METHODS: 50 170 patients from the SEER Program at the National Cancer Institute database were included in this study. All patients were diagnosed with gliomas of the brain from 2003 to 2012. Patient SES was divided into tertiles and quintiles. Treatment options included radiation (yes/no), surgery (gross total resection [GTR]/other surgery/no surgery), and radiation with surgery (yes/no). Multivariable logistic regression and Cox proportional hazards model were used to analyze data with SAS v9.4. The results were adjusted for age at diagnosis, race, and sex. Kaplan-Meier survival curves were constructed according to SES tertiles and quintiles. RESULTS: Patients from a higher SES tertile were significantly more likely to receive surgery, radiation, GTR, and radiation with surgery (odds ratio [OR] = 1.101, 1.12, 1.108, 1.153, respectively, all P < .0001). This correlation was also true when patients were divided into quintiles (OR = 1.06, 1.074, 1.065, 1.092, respectively, all P < .0001). Furthermore, the lowest SES tertiles (hazards ratio [HR] = 1.226, 1.129) and the lowest SES quintiles (HR = 1.264, 1.232, 1.178, 1.108) were associated with significantly shorter survival times (all P for trend <.0001). Surgery, surgery with radiation therapy, and GTR were also found to be associated with improved overall survival in glioma patients (HR = 0.649, 0.782, 0.753, respectively, all P < .0001). When adjusted for treatment received (radiation, surgery, or radiation with surgery), the effect of SES on survival reduced (HR = 1.204, 1.11 for tertiles; HR = 1.239, 1.198, 1.153, 1.091 for quintiles), but was still significant (all P for trend <.0001). CONCLUSION: The findings from this national study on patients with gliomas suggest an effect of SES on access to treatment and survival in patients with gliomas. Further studies are required to understand reasons underlying these disparities and how they may be addressed.